Time as a criterion for the movement of social phenomena in space - Guyvan, P. D.; Гуйван, Петро Дмитрович; Huivan, Petro D.; Гуйван, П. Д. (Одеса, 2021)
This article is devoted to the scientific study of the essence and content of temporal progress in nature, which concerns both social relations and the sphere of knowledge of various aspects of life around us. It is emphasized that the issue of time is very important worldview. After all, time in human perception is a phenomenon that is characterized by a special emotional awareness as a factor that determines the temporality of our stay on earth. Time is the all-encompassing factor that allows to make an essential connection of events and phenomena occurring in space, giving them a proper perception of their place in the system of interactions of various phenomena of a particular interaction in space. The paper emphasizes that temporal issues must always be considered in relation to the spatial, this interaction has always been an important element in the study of the world. An ontological vision of temporal processes has been studied, according to which matter as a philosophical category is perceived not through its individual specific properties, but through the general, comprehensive and abstract nature of its manifestations. This means that time, according to this theory, has a subjective manifestation, which is reproduced in the feelings and experiences of a particular person about real material phenomena, reflected in the internal duration, which creates the time of the external world. It is determined that time is a property of being itself, its ontological attribute, if an object moves in space, then, of course, it also moves in time. The paper concludes that there are serious difficulties in the process of cognition of time: time is much more closely related to various factors that determine the existence of bodies in space than is usually postulated. It is noted that the study of temporal properties has historically taken place within the notions of time as an absolute, homogeneous phenomenon that has the same parameters at all points in space, which does not exactly reproduce the real picture of life. In fact, most exact sciences operate with the concept of "real" time, which is conceptually substantiated by the thesis of A. Einstein that time is uneven, multidirectional, multidimensional and depends on the properties of the system of accounting and motion of matter. But, based on the greater simplicity of absolute Newtonian time and ease of use, the associated mechanism is used quite successfully as the simplest model of real temporal application.

Стаття присвячена науковому дослідженню питання про сутність і зміст часового поступу в природі, який стосується як cуспільних взаємин, так і сфери пізнання різних сторін буття, що нас оточує. Наголошується, що питання часу має досить вагоме світогляд- не значення, адже час у людському сприйнятті є тим явищем, яке характеризується особливою емоційністю усвідомлення як фактор, що зумовлює тимчасовість нашого перебування на землі. Час є тим всеохопним чинником, який дозволяє виявити сутнісний зв’язок подій і явищ, що відбуваються в просторі, надавши їм належної перцепції щодо місця в системі взаємодій різних явищ конкретної взаємодії в просторі. У роботі акцентується, що темпоральні питання завжди мають розглядатися у взаємовідношенні з просторовим, ця взаємодія завжди була важливим елементом вивчення світу. Досліджене онтологічне бачення темпоральних процесів, за яким матерія сприймається не через окремі її властивості, а через загальний, всебічний та абстрактний характер своїх виявів. Це означає, що час, за цією теорією, має суб’єктивний вияв, що відтворюється у відчуттях та переживаннях конкретної людини щодо реальних матеріальних явищ, відображених у внутрішній тривалості, що і створює час зовнішнього світу. Визначено, що час є властивістю самого буття, його онтологічним атрибутом, якщо об’єкт переміщується в просторі, то він, безумовно, також переміщується в часі. У роботі зроблено висновок про наявність серйозних труднощів у процесі пізнання часу: час має тісніший зв’язок із різноманітними чинниками, що зумовлюють існування тіл у просторі, ніж це постулюється. Зазначено, що дослідження темпоральних властивостей історично відбувалося в межах уявлень про час як абсолютне й однорідне явище, що має однакові параметри в усіх точках простору, що не зовсім точно відтворює реальну картину буття. Насправді, більшість точних наук оперують поняттям реального часу, який концептуально обґрунтовується тезою А. Ейнштейна, що час є нерівномірним, багатонаправленим, багатомірним та залежить від властивостей системи обліку й руху матерії. Виходячи з більшої простоти абсолютного Ньютонівського часу та зручності користування, пов’язаний із ним механізм доволі успішно використовується як найпростіша модель реального темпорального застосування.
Guyvan P. D. Time as a criterion for the movement of social phenomena in space / P. D. Guyvan // Актуальні проблеми філософії та соціології : Науково-практичний журнал / Голов. ред. С. Г. Секундант, відпов. ред. Д. В. Яковлев ; Міністерство освіти і науки України ; Національний університет "Одеська юридична академія". - Одеса, 2021. - Вип. 32. - С. 35-39. DOI https://doi.org/10.32837/apfs.v0i32.1022
Keywords: absolute time; time perception; temporal factors; абсолютний час; перцепція часу; темпоральні фактори; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::Philosophy subjects; Research Subject Categories::SOCIAL SCIENCES